Awareness and preventive practices of obesity among young women in Calabar South Local Government Area of Cross River State - Osuchukwu Easter Chukwudi; Agba Mathias; Anieche John Emenike; Agbor Eshiga Otuokwa; Obeten Joy Nelson (Sciendo, 2023)
Study aim: The purpose of this study was to ascertain how young women in Calabar South, Cross River State, were aware of the reasons and preventative measures for obesity.